1994
DOI: 10.1172/jci117040
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factors from the peripheral blood of two patients with rheumatoid arthritis are genetically heterogeneous and somatically mutated.

Abstract: We report the DNA sequences of the heavy and light chain immunoglobulin genes of 11 monoclonal rheumatoid factor (RF)-secreting lines derived from the peripheral blood of two patients with rheumatoid arthritis (RA). It is evident from immunogenetic analysis of these lines that RA-associated RF activity can arise from a wide variety of heavy and light chain genes and gene combinations. Although the RF response from our two patients shows a bias in gene usage toward those genes used to encode monoclonal RF, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 52 publications
1
20
0
1
Order By: Relevance
“…These observations suggest that in some RA patients, the fraction of B cell repertoire that has been antigendriven is substantially larger than in normal controls. Observations by others are consistent with this conclusion [19,21,22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These observations suggest that in some RA patients, the fraction of B cell repertoire that has been antigendriven is substantially larger than in normal controls. Observations by others are consistent with this conclusion [19,21,22].…”
Section: Discussionsupporting
confidence: 85%
“…However, the exact mechanisms involved in the pathologic autoantibody response in RA remain unclear. Studies of antibody structure may help to decipher the aetiology of a potentially pathologic autoantibody response in RA [8][9][10][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been confirmed that the corresponding germline gene 1 -69 [19] or DP10 [18] is indeed the main heavy chain gene encoding RF from healthy human immunized donors, from peripheral blood lymphocytes (PBL) from RA patients and from paraproteins [27]. Some of the RF-encoding germline genes reported by other authors, mainly from studies of RF-secreting hybridomas [24,28,29], occurred recurrently in our investigation, namely the 3.23/DP-47/VH26, the 3.53/DP-42, the 4.59/DP-71/4.11 and the 4.18 germline gene.…”
Section: Discussionmentioning
confidence: 96%
“…However, despite the apparent enrichment for 1 1-codon VK CDR3s in some patients with autoimmune disease, the majority of autoantibodies do not exhibit unusual K light chain CDR3 length. Most CDR3 domains of K light chains of RFs from patients with RA contain 8, 9, or 10 codons (25,(47)(48)(49)(50). Although 11-amino acid CDR3s are therefore not required for RF activity, the frequent presence of K chains with 11-amino acid CDR3s in some patients with autoimmune diseases may be a marker for an antibody repertoire that has been abnormally regulated or abnormally activated.…”
Section: Methodsmentioning
confidence: 99%